Sonothrombolysis With Transcranial Color-Coded Sonography and Recombinant Tissue-Type Plasminogen Activator in Acute Middle Cerebral Artery Main Stem Occlusion: Results From a Randomized Study - Eggers, Jürgen; König, Inke R.; Koch, Björn; Händler, Götz; Seidel, Günter (Stroke (1970), 2008)
Background and Purpose— Sonothrombolysis is a new treatment approach in acute ischemic stroke. The results of a monocenter, randomized clinical study are presented. Methods— Subjects with acute middle cerebral artery main stem occlusion were randomized into a target group receiving 1-hour transcranial continuous insonation using a 1.8-MHz Doppler ultrasound (US) probe or a control group. All underwent standard thrombolysis with intravenous recombinant tissue-type plasminogen activator. Results— Thirty-seven subjects were included; 19 subjects were treated in the target (US) group and 18 in the control (no-US) group, all with no residual flow in the middle cerebral artery main stem occlusion (Thrombolysis in Brain Ischemia recanalization grade 0). Compared with the no-US group, the US group showed greater improvement in National Institutes of Health Stroke Scale values at days 1 and 4 and a higher median Thrombolysis in Brain Ischemia grade 1 hour after recombinant tissue-type plasminogen activator initiation. Recanalization (complete or partial) after 1 hour occurred in 57.9% of the US group and 22.2% of the no-US group ( P =0.045). After 90 days, 4 subjects from the US group had a modified Rankin Score ≤1 (none from the no-US group) and 8 had a Barthel Index ≥95 (none from the no US group; P =0.106 and P =0.003, respectively). Three subjects from the US group (15.8%) developed a symptomatic intracranial hemorrhage as did one (5.6%) in the no-US group ( P =0.60). Conclusions— This small randomized study indicates a beneficial impact of transcranial ultrasound on recanalization and short-term outcome in subjects with middle cerebral artery main stem occlusion and recombinant tissue-type plasminogen activator treatment.